Customer relationship intensity and their tolerance towards purported brand scandals negatively influencing perceived CSR in consumer electronics industry - Petra Martiskova; Robert Jeyakumar Nathan; Roman Svec; Petra Vysusilova; Kamil Picha (Sustainable Futures)
This study investigates associations between customer relationship intensity and their tolerance towards purported brand scandals in the consumer electronics industry, which are believed to have a negative impact on the brand’s Corporate Social Responsibilities (CSR). The tolerance towards purported scandals was operationalized and measured quantitatively through the probability of customers repeatedly choosing the consumer electronic brand given various hypothetical scandals scenarios. A quota sampling method was applied with strict control on the age categories and gender grouping of respondents, gathering a large sample of 1,000 consumer electronic products users from a Central European country, the Czech Republic. The results from the large set of statistical data clearly show that customers' tolerance of brand scandals is associated with their relationship intensity stages with the brand i.e., Initial, Awareness, Identification, Satisfaction, Loyalty and Recommendation stages. Secondly, customers' tolerance of brand scandals associated with the brand is significantly associated with specific types of brand scandals, where some scandals are tolerated more while others are perceived to be more severe. Customers consider the use of child labor as the most severe type of brand scandal associated with a brand. Thirdly, customers at the highest stage of relationship intensity i.e., “Recommendation stage” with the electronics brand are found to have significantly highest willingness to repurchase from the brand after a scandal has occurred. This research provides novel results in the sphere of brand scandals and its perceived impact to the brand’s CSR, which plays a pivotal role in its brand sustainability.